Degree and Pattern of Hearing impairment among patients attending in Audiology department of a tertiary level Hospital in Bangladesh (Bangladesh Journal of Otorhinolaryngology, 2020)
Objectives: To determine the degree and pattern of hearing impairment among patients attending audiology department of a tertiary level hospital.Methods: This was a cross sectional observational study which was carried out in the department of audiology of National Institute of ENT(NIENT) during the period of March 2015 to June 2017. A total number of 8338 patients complaining hearing impairment were included in this study. The clinical diagnosis was established by history, detailed clinical examination including otoscopic examination and all findings were recorded. Hearing assessment was done by different hearing tests according to age and need of patient. Pure Tone Average (PTA) was done on averaging the hearing threshold at 0.5, 1 and 2 kHz.Results: In this study majority of patients (30.1%) were within 25-40 years of age and most of the patients (61.27%) were male. Mild degree of hearing loss was found to have higher prevalence (40.9%) compared to other degrees of hearing losses and more than half (52.5%) of our study population had conductive hearing loss.Conclusion: Mild degree of hearing impairment and conductive type of hearing impairment are more prevalent. Audiological evaluation especially in suspected hearing impaired patient should be a priority.Bangladesh J Otorhinolaryngol; October 2017; 23(2): 115-121